Young lunar volcanic features: Thermophysical properties and formation - Elder, C; Hayne, P; Bandfield, J; Ghent, R; Williams, J; Donaldson Hanna, K; Paige, D (Elsevier, 2017)
Irregular mare patches (IMPs) are small volcanic features on the lunar nearside with young model ages. Several formation mechanisms have been proposed including: caldera collapse, explosive outgassing, lava flow inflation, pyroclastic eruption, and regolith drainage. We present new observations of the four largest IMPs (Sosigenes, In a, Cauchy-5, and Maskelyne) using the Lunar Reconnaissance Orbiter (LRO) Diviner Lunar Radiometer (Diviner) and evaluate the formation hypotheses in the context of both previous results and the results presented here. We find that the IMPs have a rock abundance slightly higher than their surrounding terrain. Comparison of the Diviner data with thermal models excludes the possibility of extensive competent rocks within ∼15 cm of the surface at the IMPs. We also derive the thermal inertia at the four largest IMPs. Three appear to have thermal inertias slightly higher than typical regolith due to alteration by nearby craters or mass wasting from surrounding steep slopes, but Ina has a thermal inertia lower than the surrounding terrain. In particular, the largest smooth mound in Ina is the area with the lowest thermal inertia, suggesting that the material on the mound is less consolidated than typical regolith and/or contains fewer small rocks ( < 1 m). Formation by lava flows or regolith drainage is not expected to result in material with a lower thermal inertia than pre-existing regolith, so some other process such as explosive outgassing or pyroclastic eruptions must have occurred.